The Writer's Identity as Self-Dismantling Text in Julien Green's Si j'étais vous. . . - Robert Ziegler (Studies in 20th & 21st Century Literature, 1990)
Written between 1944 and 1946, Julien Green's novel Si j'étais vous . . . is one of the author's most fantastic and enigmatic texts, having generated interpretations ranging from the Freudian to the theological. Yet certain central features of the text have not yet been addressed and may lead to a different approach, one focusing on the problem of the writer's identity in his works. Despite the fact that his literary efforts are unsuccessful, Fabien is shown as being a writer like Green himself, but more importantly, he is a character in another writer's fiction. As metatext, Green's novel describes the conversion of an author into a succession of language objects which are similar and alien to him. In each of his different incarnations, Fabien transposes himself as text, marrying a residual consciousness of self to the desired attributes of his "host." Fabien's round-trip journey may, therefore, represent the process of turning the writer's reality into language, and the subsequent endeavor to resituate what that language had displaced.
Keywords: ulien Green; Si j& #x27; étais vous; Freudian; theological; writer& #x27; s identity; identity; Fabien; language objects; text; self; desirable; host; round-trip journey; journey; represent; reality; language; displaced